2019
DOI: 10.1007/s12264-019-00447-9
|View full text |Cite
|
Sign up to set email alerts
|

Orexin Receptor Antagonists as Emerging Treatments for Psychiatric Disorders

Abstract: Orexins comprise two neuropeptides produced by orexin neurons in the lateral hypothalamus and are released by extensive projections of these neurons throughout the central nervous system. Orexins bind and activate their associated G protein-coupled orexin type 1 receptors (OX1Rs) and OX2Rs and act on numerous physiological processes, such as sleep-wake regulation, feeding, reward, emotion, and motivation. Research on the development of orexin receptor antagonists has dramatically increased with the approval of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 162 publications
(193 reference statements)
1
49
0
Order By: Relevance
“…These neurons release orexin neuropeptides, OXA and OXB, which bind to and activate two Gαq-protein-coupled receptors, OX 1 R and OX 2 R 16 , which, once activated, increase intracellular calcium concentrations 54,55 . Although orexins were originally discovered for their role in regulating sleep and wakefulness 14,22 , they have now been implicated in host of other behaviors, including avoidance behavior 56 , drug-seeking behavior 23,24 , and psychosis 25 . Of interest to the current project, is the ability of both OXA and OXB to dosedependently modulate PVT neuron activity and the ability of a DORA to reverse aberrant dopamine neuron activity when administered directly in the PVT 26,27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These neurons release orexin neuropeptides, OXA and OXB, which bind to and activate two Gαq-protein-coupled receptors, OX 1 R and OX 2 R 16 , which, once activated, increase intracellular calcium concentrations 54,55 . Although orexins were originally discovered for their role in regulating sleep and wakefulness 14,22 , they have now been implicated in host of other behaviors, including avoidance behavior 56 , drug-seeking behavior 23,24 , and psychosis 25 . Of interest to the current project, is the ability of both OXA and OXB to dosedependently modulate PVT neuron activity and the ability of a DORA to reverse aberrant dopamine neuron activity when administered directly in the PVT 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…The orexin system was first discovered as a modulator of sleep and appetite, but recent studies suggest this neuropeptide system plays a pleiotropic role, regulating a variety of biological processes, such as pain, cardiovascular function, and neuroendocrine regulation [19][20][21][22] . Although the orexin system is widespread and diverse in function, recent studies have shown that targeting this system may be beneficial in treating substance use disorder as well as psychosis [22][23][24][25] . Importantly, both OXA and OXB have been shown to dose-dependently increase the firing rate of PVT neurons and increase dopamine neuron population activity, without affecting the firing rate of these neurons in vivo 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 , 27 ] Thus, block of the orexin-receptor pathway may be potentially effective for reducing the excitability of brain neurons. [ 28 ] Similar to insomnia, delirium is also a neuroexcitatory symptom. Also, the plasma levels (roughly reflecting the cerebrospinal fluid) of orexin-A, were found to be relatively higher in patients with delirium than those without, although no significant difference was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Orexin is also thought to play a role in stress response with alterations in orexin found in depression and anxiety ( 214 ). Based on the research finding that orexin levels are increased in CSF of individuals with PD ( 215 ), orexin is thought to have anxiogenic effects, leading to research on orexin-1 and orexin-2 receptor, and dual-receptor antagonists for treatment of anxiety disorders ( 216 ). Suvorexant, an orexin-1 and orexin-2 receptor antagonist, is FDA-approved for primary insomnia, and is under study in PD, comparing the drug to placebo to monitor orexin levels and response to a carbon dioxide challenge (NCT02593682).…”
Section: Novel Treatments For Anxiety Disordersmentioning
confidence: 99%